PENGARUH PDRB DAN UPAH MINIMUM TERHADAP TINGKAT PENGANGGURAN DI KOTA SURABAYA TAHUN 2010-201 - Rahmah, Dinni Elinda; ., Murgianto (JEB17 : Jurnal Ekonomi dan Bisnis, 2016)
The unemployment problem has always been an issue that needs to be solved krena so great impact on the economic and social life in a civic. So the researchers focused on melkukan research on Unemployment Rate is happening in the city of Surabaya. The objective was to determine the factors that may affect unemployment in the city of Surabaya. Researchers adjust the open unemployment as vaeriabel bound and take independent variables: the GDP and Minimum Wages in the city of Surabaya on the unemployment rate in the city of Surabaya. The data used is secondary data time series by using multiple regression analysis.The results of the study on the first model, the GDP had a negative correlation to the level of unemployment in the city of Surabaya. It is clear that any increase in the GDP, the open unemployment rate in the city of Surabaya to decline, which means the GDP is not significantly affected the unemployment rate in the city of Surabaya.The second research model, the minimum wage has a negative correlation to the unemployment rate in the city of Surabaya. It is clear that any increase in the minimum wage, the unemployment rate will decline, which means wages minimu not significantly affect the unemployment rate in the city of Surabaya.Â Keywords: Unemployment Rate, the GDP, the Minimum Wages